COMPARATIVE AND ANALYTICAL FEATURES OF THE INTERPRETATION OF THE LYRICAL HERO IN EASTERN AND WESTERN LITERATURE - Soniya Marat qizi Azimbayeva (International Journal of Literature and Language Studies, 2026)
The lyrical hero occupies a central position in poetic discourse and serves as an artistic embodiment of the author's emotions, worldview, and philosophical reflections. Despite the universal nature of lyric poetry, the interpretation of the lyrical hero varies significantly across literary traditions due to differences in cultural, historical, religious, and aesthetic contexts. Eastern literature often portrays the lyrical hero as a spiritually elevated figure striving for moral perfection, divine love, and inner harmony, whereas Western literature frequently emphasizes individuality, personal freedom, psychological conflict, and subjective experience. This study aims to examine the comparative and analytical characteristics of the lyrical hero in Eastern and Western literary traditions. Through a comparative literary approach, the research identifies common features and distinctive aspects of lyrical representation, highlighting the influence of cultural values on the formation of poetic identity. The findings contribute to a deeper understanding of intercultural literary dialogue and the evolution of lyrical expression in world literature.